School Access, Resources, and Learning Outcomes : Evidence from a Non-Formal School Program in Bangladesh - Dang, Hai-Anh; Sarr, Leopold; Asadullah, Niaz (World Bank, Washington, DC, 2017)
This study reports evidence from an unusual policy intervention- The Reaching Out of School Children (ROSC) project in Bangladesh where school grants and education allowances are offered to attract hard-to-reach children to schools comprised of a single teacher and a classroom. The operating unit cost of these schools is a fraction of that of formal primary schools. Panel data is used to investigate whether ROSC schools are effective in raising enrolment and learning outcomes. The findings suggest that there is a modest impact on school participation: ROSC schools increase enrolment probability between 9 and 18 percent for children in the two age cohorts 6 to 8 and 6 to 10. They perform as well as non-ROSC schools in terms of raising test scores, and even have positive impacts on academically stronger students. There is also strong evidence of positive externalities on non-ROSC schools in program areas. These results point to the effectiveness of a new model of non-formal primary schools that can be replicated in similar settings. This paper consists of following sections: section one gives introduction. The context for the country and the program description is provided in section two, and the data is described in section three. The impacts of the ROSC project on education outcomes as measured by student enrolment and test scores are discussed in section four and other program effects are considered in section five, with the empirical estimation frameworks being respectively detailed in each section. The relative efficiency of ROSC schools versus non-ROSC schools is discussed in section six and section seven gives conclusion.